Liver Histopathological Change and Malondialdehyde Level of Rattus Norvegicus on Administration of Curcuma Zedoaria and Paracetamol Toxic Dose - Putu Oky Ari Tania; Puja Ayu Misuari; Satya Yudhayana; Ketut Ayesha Edelwise Prayoga (Universitas Nahdlatul Ulama Surabaya, 2021)
High doses of paracetamol create necrosis in the liver and produce free radicals. When liver function decreased in a long time, it will lead to severe liver damage and it will be irreversible. Rhizome of Curcuma zedoaria has the potential effect as an antioxidant, it is assumed that its properties inhibit the formation of free radicals which formed from toxic doses of paracetamol. The aim of this study was to examine the histological structure of the liver and to determine MDA levels in the administration of C. zedoaria toxic dose and paracetamol on the Rattus norvegicus. The study was used twenty-four rats divided into four groups (positive control: CMC 0.5%; negative control: paracetamol 1.35g/kg body weight; treatment group 1 (T1): C. zedoaria 105 mg/200g and paracetamol 1.35g/kg Body weight 2 hours later, and treatment group 2 (T2): paracetamol 1.35g/ kg Body weight and C. zedoaria 105 mg/200g 2 hours later). The Kruskall-Wallis test results showed MDA level did not significantly different between groups (p = 0.087). Hepatocellular changes were observed descriptively with Hematoxylin-eosin staining. Positive control showed greater hepatocellular changes rather than other groups, hepatocyte cells were enlarged with cytoplasm showing eosinophilic granules infiltrates, enlarged irregular nuclei, nucleolus prominent, there are many necrosis cells.